A microstrip-coil integration on superconducting tunnel junctions for X-ray detection - Taino, Tohru; Nakagawa, Hiroshi; Aoyagi, Masahiro; Sato, Hiroshi; Akoh, Hiroshi; Maehata, Keisuke; Ishibashi, Kenji; Sato, Hiromi; Ikeda, Tokihiro; Otani, Chiko; Ootani, Wataru; Oku, Takayuki; et al. (IEEE transactions on applied superconductivity, 2001)
We report the first demonstration of X-ray detection by using a Superconducting Tunnel Junction (STJ) with a microstrip-coil. The STJ was fabricated based on Nb/Al/AlO/sub x//Nb integration process technology using a 2 /spl mu/m design rule. Magnetic field was applied into the STJ by the microstrip-coil to suppress the dc Josephson current instead of the conventional electromagnet. The output waveform was successfully observed by irradiation of 5.9 keV X-ray under a condition of microstrip-coil current of 20 mA at 0.4 K.